PEMANFAATAN TEPUNG BUAH LINDUR (Bruguiera gymnorrhiza) DALAM PEMBUATAN CRACKERS DENGAN PENAMBAHAN GLUTEN - Sarofa, Ulya; Yulistyani, Ratna; STP, Mardiyah (REKAPANGAN, 2012)
Lindur flour is made from  basic materials lindur fruit which  has the advantage  of the source of carbohydrate, high fiber, and mineral  content.  Making crackers with lindur fruit done proportion of lindur flour and wheat  flour whereas added gluten.The  Study aims to determine  the  effect  of the proportion  of wheat  flour: wheat gluten fruit lindur to the  physical, chemical and organoleptic lindur crackers. Research design used Completely  Randomized Design comprised two factors, factor I  is the proportion of wheat flour: flour lindur (70:30, 60:40, 50:50%) and factor II is the addition of gluten (10%, 12%, 14%). The results showed that the best treatment found  in the proportion treated flour: flour lindur 70:30 (%) and the  addition  of 14% gluten, which produces fruit crackers lindur to yield 64.800%, 3.4483% water  content, protein  content  of  9.7446  %, crude  fiber  content  of  2.5224%, 17.1463 amylopectin content, the fracture (texture) 0.2805 (N/cm2) and organoleptic tests, including a sense of 3.95 / neutral, color 4.2 / like, the texture of 4 , and aroma 3/like 3.7 / neutral.keywords: Bruguiera gymnorrhiza, crackers, gluten